The case against major displacement along Nares Strait - Dawes, Peter R.; Kerr, J. William (Meddelelser om Grønland. Geoscience, 1982)
Nares Strait is a conspicuous lineament that suggests it is the site of a fault. The conflict about magnitude of displacement has developed because the interpretation of geological data from the immediate Nares Strait region is at variance with the common interpretations of the geophysical data from the surrounding oceans, which predict Nares Strait as the site of great displacement. We summarise here the geological and geophysical data presented in this volume that indicate little or no strike-slip, vertical or oblique displacement along Nares Strait, and the conclusion is based on five categories of evidence: 1) there is present-day continuity of geological features from Ellesmere Island to Greenland, 2) the Strait is aseismic, suggesting that it is not a major crustal or lithospheric fracture, 3) a pre-drift reconstruction showing large dextral strike-slip displacement (e.g. 250km) introduces unacceptable juxtaposing of the Precambrian and Palaeozoic rock provinces, 4) a pre-drift reconstruction showing Greenland and Ellesmere Island separate obliquely by a wide gap is refuted by the geology of the Strait, 5) there are no unequivocal geological or geophysical data from the immediate Strait area, which suggest that Greenland and Ellesmere Island had an initial relative position radically different from present-day geography. On the basis of 9 regional stratigraphic and structural features and by the definition of 20 geological-geophysical markers that can be traced without apparent offset from Ellesmere Island to Greenland, we conclude that any net left-lateral, strike-slip motion along Nares Strait has been minor - in the range of 0 to 25 km. This argues strongly against the hitherto widely accepted ‘pure’ sea-floor spreading origin of Baffin Bay and the Labrador Sea and suggests that other mechanisms must have played an important part in the formation of these oceanic basins.